Influence of laser power on mechanical and microstructural behavior of Nd: YAG laser welding of Incoloy alloy 800 - Alswat Haitham M. (High Temperature Materials and Processes)
Incoloy alloy 800, a type of superalloy, is well-suited for industries that require high corrosion resistance. Laser beam welding (LBW) is an effective method for improving the quality of its joints. In this study, Incoloy alloy 800 is joined using Nd:YAG LBW by varying laser power between 2 and 3 kW with a constant welding speed of 2 m·min−1. Joints were analyzed using microscopic and mechanical testing. The observed weld zone has an hourglass shape and elongated columnar structure as well as dendrites with fine equiaxed grains. Remarkable phase changes occur due to the high cooling rate, which is associated with LBW. The reduction in mechanical properties was observed at high laser power due to the laves formation. The mode of fracture was changed from ductile to brittle while increasing the laser power.